2013
DOI: 10.1002/9780470942390.mo130157
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Rett Syndrome Symptom Improvement by Metabolic Modulators in Mecp2‐Mutant Mice

Abstract: Mouse models recapitulate many symptoms of Rett Syndrome, an X-linked disorder caused by mutations in methyl-CpG-binding protein 2 (MECP2). The study of Mecp2-null male mice has provided insight into pathogenesis of the disorder; most recently, dysregulation of cholesterol and lipid metabolism. Perisymptomatic treatment with statin drugs successfully mitigates the effects of this metabolic syndrome, increases longevity and improves motor function. Described here is a metabolic drug screening protocol and timel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2019
2019

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 26 publications
0
4
0
1
Order By: Relevance
“…29,30 In experimental studies using mice and rats, overnight fasting is commonly performed before measurement of plasma lipid levels. [31][32][33] One study has shown that fasting has significant impacts on several parameters related to lipid metabolism in the rat liver. 34 In our study, we found that the levels of TC, TG, HDL-C and LDL-C in both the chow diet group and the high cholesterol diet group showed no significant changes from baseline during 24 h of fasting and that the fasting values were similar to the corresponding plasma lipid levels in the non-fasted state.…”
Section: Discussionmentioning
confidence: 99%
“…29,30 In experimental studies using mice and rats, overnight fasting is commonly performed before measurement of plasma lipid levels. [31][32][33] One study has shown that fasting has significant impacts on several parameters related to lipid metabolism in the rat liver. 34 In our study, we found that the levels of TC, TG, HDL-C and LDL-C in both the chow diet group and the high cholesterol diet group showed no significant changes from baseline during 24 h of fasting and that the fasting values were similar to the corresponding plasma lipid levels in the non-fasted state.…”
Section: Discussionmentioning
confidence: 99%
“…In our previous successful screen using a DMD fish model we used birefringence as the primary outcome (Waugh et al, 2014), though we have successfully used movement (measured using the same methodology as described in the present screen) as an outcome for testing therapies in targeted screening in other models of related myopathies (Gibbs et al, 2013a; Robb et al, 2011; Sabha et al, 2016). The mouse screen was performed using a technical strategy that we advanced for studying a mouse model of Rett Syndrome (Buchovecky et al, 2013a,b). Our screen with the Rett Syndrome mouse used a similar number of breeding pairs, tested offspring number, and a G1 dominant modifier approach, and uncovered several genetic loci that modify the Rett mouse phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…A rapid strategy for applying forward genetics to identify modifiers in mice is to use the super mutagen N-ethyl-N-nitrosourea (ENU) (Geister et al, 2018). We have previously utilized an ENU-based genetic screen to uncover second site gene modifiers in a mouse model of Rett syndrome (Buchovecky et al, 2013a,b). To date, however, ENU mutagenesis modifier testing has yet to be applied to any mouse models of muscle disease.…”
Section: Introductionmentioning
confidence: 99%
“…For example, we could sample biomarkers in patient tissues, such as muscle, or fluids more accessible than the brain. Take for example genes involved in lipid and cholesterol metabolism, whose expression is controlled by MECP2 in brain cortex and liver (Buchovecky et al, 2013a; Kyle et al, 2016). The concept that organ-specific diseases express molecular phenotypes in multiple tissues other than the affected organ has been tested comprehensively in mouse models of organ-specific pathologies (Kozawa et al, 2018).…”
Section: Why Is Rett Syndrome An Ideal Neurodevelopmental Disorder Tomentioning
confidence: 99%